(3GdUehO ceJZjQ hSjW ddYdGbI Hjf GdGZJQGH GdfaSj hGdJhGab GdfaSj hGdGLJeGYj dOi WdGH GdLGeYI Phj GdNdajGJ GdJYdjejI GdeNJdaI (B/s - (3,CMeO dWaj YHO GdMejO jhSa MHTs; (3efGd YHO GdfYje eMeO Wgs; (3faj`S``I a``hRj Y`e```Qs (2024)
(3gOaJ GdQSGdI Edi GdJMbb ef OhQ GdUehO ceJZjQ hSjW aj GdYdGbI Hjf GdGZJQGH GdfaSj hGdJhGab GdfaSj hGdGLJeGYj, hbO JchfJ GdYjfI ef (B((3437(B) (3WGdH hWGdHI ef WdHI GdeQMdI GdLGeYjI HGdLGeYGJ GdeUQjI GdMchejI hGdNGUI HeNJda GdJNUUGJ GdfXQjI hGdYedjI HhGbY (B((3300(B) (3WGdHI, (B((3137(B) (3WGdH JJQGhM CYeGQge ef 18 Edi 27 SfI, hGfbSeJ GdYjfI Edi eLehYJjf GdChdi ef Phj GdNdajGJ GdJYdjejI GdeNJdaI hGdKGfjI ef Phj GdNdajGJ GdJYdjejI GdeJLGfSI, hJe GNJHGQ GdaQhV Ydi GdeLehYJjf, hGSJNOe ebjGS GdGZJQGH GdfaSj (B((3ef GYOGO GdHGMK(B)(3, hebjGS GdJhGab GdfaSj hGdGLJeGYj (B((3ef GYOGO GdHGMK(B)(3, h ebjGS GdUehO chfQ hOjajOSf 2003 (B((3ef JQLeI GdHGMK(B)(3, hbO GTGQJ fJGFL GdOQGSI Edi hLhO YdGbI OGdI GMUGFkjG Hjf GdJhGab GdfaSj GdGLJeGYj hGdUehO aj eLehYI GdWdGH hGdWGdHGJ ef Phj GdNdajGJ GdJYdjejI GdeJLGfSI, hCf GdUehO aj gPG GdfehPL de jJhSW GdYdGbI Hjf GdGZJQGH GdfaSj hGdJhGab GdfaSj hGdGLJeGYj dOi GdYjfI GdeJLGfSI, hCTGQJ Edi hLhO YdGbI OGdI GMUGFkjG Hjf GdJhGab GdfaSj GdGLJeGYj hGdUehO aj eLehYI GdWdGH hGdWGdHGJ ef Phj GdNdajGJ GdJYdjejI GdeNJdaI, hCf GdUehO jJhSW LRFkjG GdYdGbI Hjf GdGZJQGH GdfaSj dOi YjfI GdWdGH Phj GdNdajGJ GdJYdjejI GdeNJdaI Cj Cfg cdeG GQJaY GdUehO dOi GdWdHI ef Phj GdNdajGJ GdJYdjejI GdeNJdaI GfNaV TYhQge HGdGZJQGH GdGZJQGH GdfaSj eeG jDKQ Ydi GQJaGY GdJhGab GdfaSj hGdGLJeGYj dOjge(B.s
This study aimed to investigate the mediating role of resilience in the relationship between psychological alienation, psychological and social adjustment. The sample consisted of 437 male and female university students from various theoretical and practical specializations in Egyptian government and private universities, aged 18-27 years, The study sample was divided into two groups, the first consisting of individuals with different educational backgrounds, and the second consisting of individuals with homogeneous educational backgrounds. The hypotheses were tested on both groups.The Psychological Alienation Scale (prepared by the researcher), Psychological and Social Adjustment Scale (prepared by the researcher), and Connor-Davidson Resilience Scale (translated by the researcher) were used to collect data. Results showed that resilience plays a mediating role in the relationship between psychological alienation and psychological and social adjustment in the group of students with different educational backgrounds. These findings suggest the importance of resilience in promoting resilience among university students.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B89-94.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdJYdje GdLGeYis; (3WdHI GdLGeYGJs -- (3Yde faSs; (3GdUehOs -- (3GdGZJQGH GdfaSjs -- (3GdJhGab GdfaSj hGdGLJeGYjs